2021
DOI: 10.1021/acs.jmedchem.0c02147
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Acidity of 5-(m-Terphenyl-2′-yl)-1H-tetrazoles: Evidence for an Enhanced Polar−π Effect Compared to Carboxylic Acids

Abstract: The polar−π effect on tetrazoles, medicinal chemistry isosteres of carboxylate, is tested by a Hammett pK a (microtitration) analysis over a series of 5-(m-terphenyl-2′-yl)-1H-tetrazoles. A comparison with m-terphenyl-2′-yl-carboxylic acids supports the isostere analogy also in response to environmental changes. Computational (B97D/def2TZVPPD) extension of the series plus a scan of solvents (vacuum to water) demonstrates the trend with the dielectric constant. The effect is energetically small but may make sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 40 publications
1
6
0
Order By: Relevance
“…Plotting the p K a values of para-substituted imidazoles 1–5 against the Hammett σ values revealed a good linear correlation with ρ = 0.65 and R 2 = 0.95. The p K a values of the conjugated acid of the imidazoles 1–6 are in the range 4.6–5.8, which are comparable to another heterocycle tetrazole that showed a comparable ρ value of 0.86 . It is apparent that the p K a values of the imidazoles are affected by the presence of substituents at distant position of flanking aromatic rings; electron-donating groups (e.g., OMe, Me) make imidazoles more basic, whereas electron-withdrawing groups (e.g., F, CF 3 ) make imidazoles less basic.…”
Section: Results and Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…Plotting the p K a values of para-substituted imidazoles 1–5 against the Hammett σ values revealed a good linear correlation with ρ = 0.65 and R 2 = 0.95. The p K a values of the conjugated acid of the imidazoles 1–6 are in the range 4.6–5.8, which are comparable to another heterocycle tetrazole that showed a comparable ρ value of 0.86 . It is apparent that the p K a values of the imidazoles are affected by the presence of substituents at distant position of flanking aromatic rings; electron-donating groups (e.g., OMe, Me) make imidazoles more basic, whereas electron-withdrawing groups (e.g., F, CF 3 ) make imidazoles less basic.…”
Section: Results and Discussionmentioning
confidence: 73%
“…The pK a values of the conjugated acid of the imidazoles 1−6 are in the range 4.6−5.8, which are comparable to another heterocycle tetrazole that showed a comparable ρ value of 0.86. 34 It is apparent that the pK a values of the imidazoles are affected by the presence of substituents at distant position of flanking aromatic rings; electron-donating groups (e.g., OMe, Me) make imidazoles more basic, whereas electron-withdrawing groups (e.g., F, CF 3 ) make imidazoles less basic. Despite the fact that the meta-substituted F has a significantly different σ value than the para-substituted F (0.34 vs 0.06, respectively), their pK a values are very similar (5.07 and 5.17 for m-F and p-F, respectively).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to examinations of π–π stacking interactions, fluorinated aromatic molecules have found applications as probes for physical-organic studies of cation−π interactions in protein science. ,, In this regard, our work demonstrates that the fluorination strategy can be effectively applied to studies of the underlying noncovalent interactions in cyclophanes. More generally, we highlight that, along with molecular balances and 2,6-diarylaromatic systems, cyclophanes are powerful model systems for probing noncovalent interactions involving aromatic rings, an area of current chemical and biological interest.…”
Section: Discussionmentioning
confidence: 99%
“…Siegel et al . recently reported that the acidity of tetrazoles correlates well with Hammett sigma values, indicating the presence of polar‐π interactions between tetrazole and neighboring rings in 2,6‐diaryl aromatic systems [8d] . However, a critical structural support and in‐depth theoretical analysis of its physical nature have not been analyzed yet.…”
Section: Introductionmentioning
confidence: 99%